A prospective study to determine the incidence, clinical profile, and outcomes of patients with ventilator-associated pneumonia - Sagnik Bhattacharjee; Annie B Khyriem; Clarissa Jane Lyngdoh; Abhijit Kumar Prasad (Wolters Kluwer Medknow Publications, 2023)
Objective: The objective was to determine the incidence, etiological agents, and antibiotic susceptibility pattern of isolates causing ventilator-associated pneumonia (VAP). Methods: The prospective observational study was carried out on 146 adults admitted to the hospital, who were put on mechanical ventilation for a minimum period of 48 h at NEIGRIHMS, Shillong. The study was conducted for 1 year from December 2019 to December 2020. VAP was diagnosed as per the Clinical Pulmonary Infection Score. Demographic, clinical characteristics, culture reports, and antibiotic susceptibility of the patients were noted. Patients were followed up till discharge or death. Outcome measures were risk factors for VAP and mortality. Results: We report an incidence of VAP as 10.6/1000 ventilator days. The predominant organisms seen were Acinetobacter baumannii (62.33%), Klebsiella pneumoniae (47.26%), and Pseudomonas aeruginosa (19.18%). 33/146 (22.6%) patients expired, among which 17 patients had VAP (40.48% vs. 15.38%, P = 0.001). VAP patients had significantly higher odds of smoking (odds ratio [OR] = 2.412, P = 0.016), more polybacterial infections (OR = 2.271, P = 0.024), and more mortality (OR = 3.681, P = 0.001). Among the organisms, P. aeruginosa (OR = 0.115, P = 0.013) and K. pneumoniae (OR = 6.818, P = 0.003) were significantly associated with mortality in patients with VAP. Conclusion: We report an incidence of VAP as 10.6/1000 ventilator days among intensive care unit patients. Smoking was a significant risk factor for VAP. VAP patients had a significantly higher risk of mortality with K. pneumoniae and P. aeruginosa being significant organisms responsible for it.